Environment-friendly water-based two-component polyurethane coating and preparation method thereof
Through the coordinated design of dynamic disulfide bond-photo-responsive isocyanate curing agent and nano SiO2@POSS and silicone modified resin, the balance between storage stability, low-temperature curing and coating film functionality is solved, and the high-performance self-repair effect of light excitation curing and coating film at room temperature is achieved.
Patent Information
- Application Number
- CN202510644973.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-06-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aqueous two-component polyurethane coatings are difficult to achieve a balance between storage stability, low-temperature curing characteristics and coating film functionality, especially lacking an environmentally friendly system that can trigger curing at room temperature and has the ability to self-heal the damage.
Using dynamic disulfide bond-photoresponsive isocyanate curing agent, a coating system that can cure at room temperature is designed through the combination of hyperbranched polyester framework, dynamic disulfide bond, ortho-nitrobenzyl ester group and urethane bond is designed, and the hardness and water resistance of the coating film are improved through the synergistic effect of nano SiO2@POSS and siloxane modified resin.
It achieves the stability extension of the coating during the storage stage, the low temperature and high efficiency of the curing process, the high mechanical strength, crack resistance and self-repair ability of the coating film, and meets the needs of low VOC emissions and high performance.
Smart Images

Figure CN120173492A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coatings, and particularly relates to an environment-friendly waterborne two-component polyurethane coating and a preparation method thereof. Background Art
[0002] Traditional two-component polyurethane coatings are widely used in the fields of industrial protection and decoration. However, their solvent-based systems contain a large amount of volatile organic compounds (VOCs), causing environmental pollution and health hazards. In recent years, although waterborne two-component polyurethane coatings can reduce VOC emissions, conventional isocyanate curing agents are prone to side reactions with moisture, resulting in poor storage stability and short pot life. In addition, the existing waterborne systems are still difficult to reach the level of solvent-based coatings in terms of film hardness, water resistance and other properties, restricting their application in harsh environments.
[0003] In the prior art, physical coating or chemical blocking techniques are often used to extend the pot life of waterborne systems. However, the physical coating method is prone to incomplete release of the curing agent, affecting the crosslinking density; the chemical blocking method requires high temperature (usually >100°C) for deblocking, with high energy consumption and inapplicable to heat-sensitive substrates. On the other hand, once the traditional polyurethane film forms a permanent crosslinked network, it lacks self-healing ability and cannot restore the protective performance after mechanical damage, shortening the service life of the coating.
[0004] With the increasingly strict environmental protection regulations, the market urgently demands waterborne coatings with both low VOC emissions and high performance. However, it is difficult for the prior art to achieve a balance among storage stability, low-temperature curing characteristics and film functionality, especially lacking an environment-friendly system that can trigger curing at room temperature and has damage self-healing ability. These problems restrict the popularization and application of waterborne two-component polyurethane coatings in high-value-added fields. Summary of the Invention
[0005] The present application provides an environment-friendly waterborne two-component polyurethane coating, including component A and component B, and the mass ratio of component A to component B is 3:1 - 5:1; component A contains the following components by mass percentage: 50 - 70% of waterborne hydroxyl acrylic resin, 3 - 8% of nano-SiO2@POSS, 0.2 - 0.8% of wetting agent, 0.1 - 0.5% of defoaming agent, and the balance is deionized water; component B contains the following components by mass percentage: 80 - 95% of dynamic disulfide bond-photo-responsive isocyanate curing agent, 1 - 3% of photoinitiator, 0.5 - 2% of leveling agent, 3 - 10% of co-solvent; wherein, the dynamic disulfide bond-photo-responsive isocyanate curing agent is a hyperbranched polyester derivative, including a hyperbranched polyester backbone, dynamic disulfide bonds, o-nitrobenzyl ester groups and urethane bonds.
[0006] In some embodiments, the aqueous hydroxy acrylic resin is a silicone-modified acrylic copolymer. The aqueous hydroxy acrylic resin is copolymerized from methyl methacrylate, butyl acrylate, and 2-hydroxyethyl methacrylate, and a silane coupling agent KH-550 is added during the copolymerization. The side chain of the aqueous hydroxy acrylic resin contains siloxane groups, and the hydroxyl value is 80-120 mg KOH / g.
[0007] In some embodiments, the mass ratio of SiO2 to POSS in the nano-SiO2@POSS is 1:1, and the particle size of SiO2 is 15-25 nm.
[0008] In some embodiments, in the dynamic disulfide bond-photoresponsive isocyanate curing agent, the content of the dynamic disulfide bond is 5-8 wt%.
[0009] In some embodiments, the wetting agent is a polyether-modified silicone with a molecular weight of 800-1200 g / mol; the defoaming agent is a mineral oil-polyether composite defoaming agent with an HLB value of 3-5; the photoinitiator is a benzophenone derivative; the leveling agent is a fluorocarbon-modified polyacrylate; and the cosolvent is dipropylene glycol dimethyl ether.
[0010] The present application also provides a preparation method of the environmentally friendly waterborne two-component polyurethane coating as described in any one of the foregoing, comprising the following steps: S11. React methyl methacrylate, butyl acrylate, 2-hydroxyethyl methacrylate and silane coupling agent KH-550 at a mass ratio of 40:35:20:5 under the condition of an initiator, react at 80±2 °C for 4-5 h to obtain a silicone-modified acrylic resin; S12. Ball-mill nano-SiO2 and octavinylsilsesquioxane at a mass ratio of 1:1 for 2-3 h to prepare a nano-SiO2@POSS dispersion; S13. Mix the resin obtained in S11, the dispersion obtained in S12 with a wetting agent, an antifoaming agent and deionized water, disperse at 1200-1500 rpm for 30-40 min to obtain component A; S21. Melt and polycondense pentaerythritol, adipic acid, 3-mercaptopropionic acid, acrylic acid, 2-hydroxyethyl methacrylate at a mass ratio of 10:50:20:10:10 at 160-180 °C for 6 h to obtain hyperbranched polyester HBP; S22. React the hyperbranched polyester HBP with I2 at a molar ratio of 2:1 to construct dynamic disulfide bonds to obtain HBP with dynamic disulfide bonds; S23. Mix the HBP with dynamic disulfide bonds and o-nitrobenzyl alcohol at a molar ratio of 1:10 for an esterification reaction to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups; S24. React the HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups with hexamethylene diisocyanate at a molar ratio of 1:15 at 60 °C for 6 h to prepare a dynamic disulfide bond-photoresponsive isocyanate curing agent; S25. Ultrasonically disperse the dynamic disulfide bond-photoresponsive isocyanate curing agent with a photoinitiator, a leveling agent and a cosolvent for 20-30 min to obtain component B; S30. Mix the component A and the component B in proportion and irradiate with 365 nm UV for 30-60 s to trigger curing.
[0011] In some embodiments, in the copolymerization reaction of S11, the initiator for the copolymerization reaction is ammonium persulfate, and the dosage of the initiator is 0.4-0.6% of the total mass of methyl methacrylate, butyl acrylate and 2-hydroxyethyl methacrylate.
[0012] In some embodiments, in S22, the construction of the dynamic disulfide bond is carried out in an ethanol / water mixed solvent with a volume ratio of 1:1, under nitrogen protection, the reaction time is 12 h, and the reaction temperature is 25 °C.
[0013] In some embodiments, in S23, the temperature of the isocyanate esterification reaction is 55-65 °C.
[0014] In some embodiments, in S30, the UV irradiation intensity is 40-60 mW / cm², and the coated film is cured assistantly at 40-50 °C for 0.5-1 h after irradiation.
[0015] The above technical solutions provided by the embodiments of the present application have the following advantages compared with the prior art: 1. Through the molecular design of the dynamic disulfide bond-photo-responsive isocyanate curing agent, the isocyanate group is chemically shielded by the o-nitrobenzyl ester group and the hydrophobic encapsulation of the hyperbranched polyester backbone, so that the hydrolysis side reaction of the coating is significantly inhibited during storage, and the storage stability is prolonged.
[0016] 2. By UV irradiation to trigger the cleavage of the o-nitrobenzyl ester group of the photoinitiator to release the active -NCO, and form a polyurethane main crosslinking network with the hydroxyl acrylate resin. At the same time, the dynamic disulfide bond is reversibly recombined during curing to form an auxiliary network, so that the coating film has both high mechanical strength, crack resistance and self-healing ability.
[0017] 3. Through the synergistic effect of nano-SiO2@POSS and the silicone-modified acrylic resin, the interpenetrating network of SiO2 and POSS fills the micropores, and the silicone groups migrate to form a surface hydrophobic layer, so that the hardness of the coating film is improved, the water and oxygen permeability is reduced, and the chemical corrosion resistance is enhanced.
[0018] 4. By precisely controlling the molar ratio of hydroxyl group to isocyanate group, the crosslinking density reaches equilibrium, which not only ensures the completeness of the reaction, but also avoids side reactions caused by excessive -NCO, ensuring the optimal comprehensive performance of the coating film.
[0019] 5. Through the parameter design of UV light intensity and low-temperature assisted curing, the curing process is fast and efficient, the dynamic bond network is fully reconstructed, and at the same time, the energy consumption is reduced and it is adapted to heat-sensitive substrates.
[0020] 6. Through the synergy of the high functionality of the dynamic disulfide bond-photo-responsive isocyanate curing agent and the content of the dynamic disulfide bond, the optimal ratio between the self-healing function and the mechanical properties of the coating film is achieved, avoiding softening or a decrease in solvent resistance.
[0021] 7. Through the matching design of the hydroxyl value of the silicone-modified resin and the particle size of nano-SiO2@POSS, the interfacial compatibility between the resin matrix and the inorganic particles is enhanced, the dispersion uniformity is improved, and the denseness of the coating film is significantly optimized. Description of the Drawings
[0022] The drawings here are incorporated into the specification and form a part of this specification, showing the embodiments in line with the present invention, and are used together with the specification to explain the principles of the present invention.
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, for those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0024] Figure 1 Flow chart of a preparation method of an environment-friendly waterborne two-component polyurethane coating provided by an embodiment of the present application. Detailed implementation manners
[0025] To make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are some but not all of the embodiments of the present application. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present application without creative efforts shall fall within the scope of protection of the present application.
[0026] The present application provides an environment-friendly waterborne two-component polyurethane coating, including component A and component B. The mass ratio of component A to component B is 3:1 - 5:1. Component A contains the following components by mass percentage: 50 - 70% of waterborne hydroxyl acrylic resin, 3 - 8% of nano-SiO2@POSS, 0.2 - 0.8% of wetting agent, 0.1 - 0.5% of defoaming agent, and the balance is deionized water. Component B contains the following components by mass percentage: 80 - 95% of dynamic disulfide bond-photo-responsive isocyanate curing agent, 1 - 3% of photoinitiator, 0.5 - 2% of leveling agent, and 3 - 10% of cosolvent. Among them, the dynamic disulfide bond-photo-responsive isocyanate curing agent is a hyperbranched polyester derivative, including a hyperbranched polyester backbone, dynamic disulfide bonds, o-nitrobenzyl ester groups, and urethane bonds. The molar ratio of the hydroxyl group of the waterborne hydroxyl acrylic resin in component A to the isocyanate group of the dynamic disulfide bond-photo-responsive isocyanate curing agent in component B is 1:1.05 - 1:1.2.
[0027] Specifically, 4 - 6 dynamic disulfide bonds (—S—S—), 4 - 6 o-nitrobenzyl ester groups (—COO-ONB), and 8 - 12 urethane bonds (—O-CONH-(CH2)6-NCO) are connected to the hyperbranched polyester backbone (HBP) of each dynamic disulfide bond-photo-responsive isocyanate curing agent molecule.
[0028] The stability of the coating is achieved through the molecular design of the dynamic disulfide bond-photo-responsive isocyanate curing agent during the storage stage. The o-nitrobenzyl ester groups in the curing agent shield the isocyanate groups through covalent bonds, preventing them from pre-reacting with the hydroxyl groups in component A or environmental moisture. At the same time, the three-dimensional structure of the hyperbranched polyester backbone (HBP) wraps the —NCO groups in the hydrophobic core, reducing contact with the aqueous phase and inhibiting hydrolysis side reactions, thereby extending the storage period. The siloxane-modified acrylic resin in component A enhances the hydrophobicity through the side-chain siloxane groups, improves the compatibility with component B, and further reduces the risk of phase separation.
[0029] During the mixing process, components A and B are mixed in a ratio of 3:1 - 5:1 to form a homogeneous emulsion. The wetting agent (polyether-modified silicone) in component A reduces the surface tension of the system and improves the wettability of the substrate; the defoaming agent (mineral oil-polyether composite) inhibits the generation of bubbles during stirring to ensure a smooth coating film. The co-solvent (dipropylene glycol dimethyl ether) in component B adjusts the viscosity and promotes the uniform dispersion of the two phases. At this time, the dynamic disulfide bonds remain stable, but provide a structural basis for the bond reorganization in the subsequent curing stage.
[0030] In the curing stage, UV irradiation triggers the photoinitiator (benzophenone derivative), causing the photolysis cleavage of the o-nitrobenzyl ester group and releasing the active -NCO group. The released -NCO undergoes an addition reaction with the -OH of the hydroxy acrylic resin in component A to form the polyurethane main crosslinking network (-NHCOO-). Meanwhile, the dynamic disulfide bonds undergo reversible cleavage and reorganization during curing through thermal or mechanical stimulation to form an auxiliary crosslinking network, relieving internal stress and preventing the coating film from cracking. The nano-SiO2@POSS in component A fills the micropores of the coating film through the interpenetrating network of SiO2 and POSS, reducing the water and oxygen permeability and synergistically enhancing the hardness and water resistance.
[0031] After the coating film is formed, the side-chain siloxane groups of the siloxane-modified acrylic resin migrate to the surface to form a low-surface-energy hydrophobic layer, enhancing the stain resistance and chemical corrosion resistance. The dynamic disulfide bond network endows the coating film with self-healing ability: when scratched, local heating to 60 - 80 °C or UV irradiation can break the disulfide bonds and redistribute them, enabling the reconnection of molecular chains and restoring the continuity of the coating film. The hyperbranched structure ensures a high crosslinking density through high functionality, compensating for the possible loss of mechanical properties caused by the dynamic bond reorganization.
[0032] The final coating film achieves the self-healing function of damage while maintaining high hardness (contributed by nano-SiO2@POSS) and water resistance (siloxane hydrophobic layer) through the synergistic effect of the main crosslinking network and the dynamic auxiliary network. The molar ratio of hydroxyl groups to isocyanate groups is controlled at 1:1.05 - 1:1.2, which not only ensures the completeness of the reaction but also avoids side reactions caused by excessive -NCO, achieving a balance in the comprehensive performance of the coating film.
[0033] Through the synergistic design of a dynamic disulfide bond-photoresponsive isocyanate curing agent, the isocyanate group and the hydrophobic encapsulation of the hyperbranched polyester backbone (HBP) are chemically shielded by the o-nitrobenzyl ester group during the storage stage, significantly improving the storage stability of the coating and inhibiting the hydrolysis side reaction; during the curing stage, UV is used to trigger the release of active -NCO for efficient crosslinking with the hydroxyl acrylic resin in Component A, and the reversible recombination of the dynamic disulfide bond forms a double network, endowing the coating film with self-healing ability and crack resistance; meanwhile, the nano-SiO2@POSS and the silicone-modified resin in Component A synergistically enhance the hardness, water resistance and hydrophobic barrier function of the coating film, the low-viscosity cosolvent and wetting agent in Component B ensure the construction leveling property, and the molar ratio of hydroxyl group to isocyanate group (1:1.05 - 1:1.2) precisely controls the crosslinking density, ultimately achieving the unity of low VOC emissions, low-temperature curing (40 - 50 °C) and high-performance coating film characteristics.
[0034] In some embodiments, the aqueous hydroxyl acrylic resin is a silicone-modified acrylic copolymer, which is copolymerized from methyl methacrylate, butyl acrylate and 2-hydroxyethyl methacrylate, and a silane coupling agent KH-550 is added during the copolymerization. The side chain of the aqueous hydroxyl acrylic resin contains a siloxane group, and the hydroxyl value is 80 - 120 mg KOH / g.
[0035] The aqueous hydroxyl acrylic resin forms a rigid-flexible balanced main chain structure through the copolymerization of methyl methacrylate (MMA) and butyl acrylate (BA). 2-Hydroxyethyl methacrylate (HEMA) provides hydroxyl groups to react with the isocyanate curing agent in Component B to form a polyurethane crosslinking network. After hydrolysis, the silane coupling agent KH-550 generates silanol NH2(CH2)3Si(OH)3. The silanol and 2-hydroxyethyl methacrylate monomer condense to form Si-O-C, and the other hydroxyl groups connected to Si further condense with silanol to form a siloxane, thereby grafting and introducing a siloxane group (—Si—O—(CH2)3—NH2) into the resin side chain; during the curing process of the coating film, the siloxane group hydrolyzes to generate silanol groups (—Si—OH), which further condense to form a Si—O—Si three-dimensional network and migrate to the surface of the coating film to form a dense hydrophobic barrier. At the same time, the hydroxyl value of 80 - 120 mg KOH / g ensures sufficient crosslinking with the isocyanate group while avoiding excessive hydrophilicity of the resin by regulating the hydroxyl density, maintaining the balance of the water resistance and mechanical properties of the coating film.
[0036] In some embodiments, the mass ratio of SiO2 to POSS in the nano-SiO2@POSS is 1:1, and the particle size of SiO2 is 15 - 25 nm.
[0037] The nano-SiO2@POSS is formed by compounding SiO2 nanoparticles and cage-like polyhedral oligomeric silsesquioxane (POSS) in a mass ratio of 1:1 to form an interpenetrating reinforcement structure. Among them, the surface of 15-25 nm SiO2 particles is physically entangled and partially chemically bonded with the octavinyl groups of POSS through ball milling dispersion. The cage-like skeleton (Si8O 12 ) of POSS interpenetrates the gaps between SiO2 particles in the coating film to form a three-dimensional network filling micropores. This composite structure balances the contributions of inorganic rigidity (SiO2) and organic toughness (POSS) through a mass ratio of 1:1. The 15-25 nm particle size of SiO2 not only avoids the agglomeration tendency caused by too small a size but also ensures topological matching with POSS, enabling the coating film to maintain good flexibility while improving hardness and water resistance. The cage-like structure of POSS also reduces the propagation of thermal stress cracks by restricting the movement of resin segments, achieving the synergistic optimization of high hardness, low water absorption, and anti-cracking properties.
[0038] In some embodiments, the content of dynamic disulfide bonds in the dynamic disulfide bond-photo-responsive isocyanate curing agent is 5-8 wt%.
[0039] During the curing stage, the dynamic disulfide bonds participate in the network construction as auxiliary cross-linking points. Their content of 5-8 wt% ensures that there is a sufficient density of dynamic bonds to trigger self-healing (recombination after the breakage of —S—S— bonds) when the coating film is heated or mechanically stimulated (such as at 60-80 °C), while avoiding excessive dynamic bonds from weakening the initial mechanical strength of the main cross-linked network; during the storage stage, the appropriate content of dynamic bonds reduces the risk of premature activation of isocyanate groups (—NCO) caused by excessive molecular chain movement, and cooperates with the shielding effect of the photocage protection group to maintain the stability of component B. This content range achieves the optimal ratio between the self-healing efficiency and durability of the coating film. It can restore the protection continuity through the recombination of dynamic bonds when damaged, avoid softening of the coating film or a decrease in solvent resistance due to too many dynamic bonds, and at the same time ensure that the functionality of the hyperbranched backbone (HBP) of the curing agent effectively supports the cross-linking density, ultimately realizing the synchronous optimization of the self-healing function and mechanical properties.
[0040] In some embodiments, the wetting agent is a polyether-modified silicone with a molecular weight of 800-1200 g / mol; the defoaming agent is a mineral oil-polyether composite defoaming agent with an HLB value of 3-5; the photoinitiator is a benzophenone derivative; the leveling agent is a fluorocarbon-modified polyacrylate; the co-solvent is dipropylene glycol dimethyl ether.
[0041] Figure 1 The flowchart of a preparation method of a nano-alkenyl gas desorbent provided by an embodiment of the present application is shown.
[0042] As Figure 1As shown, the present application also provides a preparation method of the environmentally friendly waterborne two-component polyurethane coating as described in any one of the foregoing, comprising the following steps: S11. React methyl methacrylate, butyl acrylate, 2-hydroxyethyl methacrylate and silane coupling agent KH-550 at a mass ratio of 40:35:20:5 under the condition of an initiator, and react at 80±2 °C for 4-5 h to obtain a silicone-modified acrylic resin; S12. Ball mill nano-SiO2 and octavinylsilsesquioxane at a mass ratio of 1:1 for 2-3 h to prepare a nano-SiO2@POSS dispersion; S13. Mix the resin obtained in S11, the dispersion obtained in S12 with a wetting agent, an antifoaming agent and deionized water, and disperse at 1200-1500 rpm for 30-40 min to obtain component A; S21. React pentaerythritol, adipic acid, 3-mercaptopropionic acid, acrylic acid and 2-hydroxyethyl methacrylate at a mass ratio of 10:50:20:10:10 by melt polycondensation at 160-180 °C for 6 h to obtain hyperbranched polyester HBP; S22. React the hyperbranched polyester HBP with I2 at a molar ratio of 2:1 to construct dynamic disulfide bonds to obtain HBP with dynamic disulfide bonds; S23. Mix the HBP with dynamic disulfide bonds and o-nitrobenzyl alcohol at a molar ratio of 1:10 for an esterification reaction to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups; S24. React the HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups and hexamethylene diisocyanate at a molar ratio of 1:15 at 60 °C for 6-7 h to prepare a dynamic disulfide bond-photoresponsive isocyanate curing agent; S25. Ultrasonically disperse the dynamic disulfide bond-photoresponsive isocyanate curing agent with a photoinitiator, a leveling agent and a cosolvent for 20-30 min to obtain component B; S30. Mix the component A and the component B in proportion and irradiate with 365 nm UV for 30-60 s to trigger curing.
[0043] In the preparation of Component A, in Step S11, methyl methacrylate (hard monomer), butyl acrylate (soft monomer), and 2-hydroxyethyl methacrylate (hydroxyl-containing monomer) are copolymerized in a ratio of 40:35:20, combined with 5% KH-550 silane coupling agent, and a silicone-modified acrylic resin main chain is formed by free radical polymerization at 80±2°C. The silicone groups on its side chains form a hydrophobic layer during subsequent hydrolysis; in Step S12, nano-SiO2 and octavinyl-POSS are ball-milled at a ratio of 1:1 for 2-3 h, and the vinyl groups of POSS are physically entangled with the surface of SiO2 by mechanical force to form an inorganic-organic composite dispersion; in Step S13, the resin, nano-composite, and additives are uniformly mixed by high-speed dispersion. The wetting agent reduces the interfacial tension, and the defoaming agent inhibits the residual bubbles. In the preparation of Component B, in Step S21, pentaerythritol (tetra-functional), adipic acid (flexible chain segment), 3-mercaptopropionic acid (containing —SH), acrylic acid (containing —COOH), and 2-hydroxyethyl methacrylate (containing —OH) are polycondensed in a ratio of 10:50:20:10:10 to generate a hyperbranched polyester HBP with mercapto, carboxyl, and hydroxyl groups, and its three-dimensional structure provides dynamic bonding grafting sites; in Step S22, a dynamic disulfide bond (—S—S—) is constructed by reacting HBP with I2 in a molar ratio of 2:1; in Step S23, o-nitrobenzyl alcohol is grafted; in Step S24, the —NCO is shielded by grafting a urethane bond to form a photo-responsive curing agent; in Step S25, ultrasonic dispersion ensures that the photoinitiator is uniformly distributed in Component B. Finally, in Step S30, the cleavage of ONB is triggered by 365 nm UV irradiation to release —NCO, which reacts with the hydroxyl groups in Component A to form a main crosslinking network. At the same time, the dynamic disulfide bond constructs a reversible auxiliary network during the curing process.
[0044] In S11, the monomer ratio and the dosage of KH-550 can control the hydroxyl value (80-120 mg KOH / g) and the silicone content of the resin, ensuring the balance between crosslinking activity and hydrophobicity; the 1:1 mass ratio ball-milling in S12 enables SiO2 and POSS to form an interpenetrating reinforcement structure, and the 15-25 nm SiO2 particle size avoids agglomeration and improves dispersibility; in S21-S23, the synthesis of the hyperbranched polyester and the step-by-step grafting of dynamic bonds / photosensitive groups ensure the storage stability (shielded by ONB) and high functionality of the curing agent; the UV-triggered curing (30-60 s) in S30 combined with the thermo-responsive characteristics of the dynamic bond realizes efficient crosslinking at low temperature (40-50°C); the dispersion parameters (1200-1500 rpm, ultrasonic for 20-30 min) in the preparation of Component A and B ensure the uniform distribution of nanoparticles and additives. The leveling agent (fluorocarbon-modified polyacrylate) and the co-solvent (dipropylene glycol dimethyl ether) synergistically improve the construction leveling property, and finally an environmentally friendly coating with high hardness, self-healing, low VOC, and excellent storage stability is obtained.
[0045] In some embodiments, in the copolymerization reaction of S11, the initiator of the copolymerization reaction is ammonium persulfate, and the dosage of the initiator is 0.4-0.6% of the total mass of methyl methacrylate, butyl acrylate and 2-hydroxyethyl methacrylate.
[0046] Ammonium persulfate decomposes in an aqueous phase system at 80±2 °C to generate sulfate radicals, initiating the copolymerization reaction of the three acrylic monomers. The dosage range of 0.4-0.6% controls the molecular weight of the copolymer within 50,000-80,000 Da, and the hydroxyl value is stabilized within the designed range of 80-120 mgKOH / g. This not only ensures the sufficient crosslinking activity between the hydroxyl groups of component A and -NCO of component B, but also maintains the viscosity of the resin solution (200-500 mPa·s) through a moderate molecular chain length, ensuring the uniform mixing of the nano-SiO2@POSS dispersion with the wetting agent and defoaming agent, and finally forming a dense coating film structure with the directional migration of siloxane groups, achieving the balance between high crosslinking density and flexibility.
[0047] In some embodiments, in S22, the construction of the dynamic disulfide bond reacts in an ethanol / water mixed solvent with a volume ratio of 1:1, under nitrogen protection, the reaction time is 12 h, and the reaction temperature is 25 °C. In S23, the isocyanation reaction temperature is 55-65 °C.
[0048] The construction of the dynamic disulfide bond in S22 is completed by reacting hyperbranched polyester HBP with iodine in an ethanol / water mixed solvent at 25 °C for 12 h. The reaction time of 12 h can avoid excessive crosslinking resulting in too strong rigidity of the hyperbranched polyester (HBP) skeleton; the isocyanation reaction temperature in S23 is controlled at 55-65 °C. This range not only meets the activation energy requirements (50-70 °C) of the carbamate esterification reaction between hexamethylene diisocyanate (HDI) and the hydroxyl groups in HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups, but also avoids premature decomposition of the photosensitive groups or cleavage of the dynamic disulfide bonds due to too high temperature. By setting this parameter combination, the density of the dynamic disulfide bond (5-8 wt%) and the grafting efficiency of the photosensitive groups are balanced, which not only ensures the chemical shielding stability of -NCO during the storage of the curing agent, but also ensures that the release rate of -NCO after UV triggering is synchronized with the main crosslinking reaction, achieving the purpose of synergistically improving the self-healing function and mechanical strength of the coating film, and at the same time avoiding the influence of side reactions (such as self-polymerization of HDI) at high temperature on the viscosity of component B.
[0049] In some embodiments, in S30, the UV irradiation light intensity is 40-60 mW / cm², and the coated film is cured assistedly at 40-50 °C for 0.5-1 h after irradiation.
[0050] In S30, the UV irradiation intensity of 40 - 60 mW / cm² causes the photoinitiator (benzophenone derivative) to absorb 365 nm photons to generate free radicals, triggering the photolytic cleavage of the o-nitrobenzyl ester group and releasing the active isocyanate group. The lower limit of the light intensity of 40 mW / cm² ensures that the ONB cleavage rate is > 80% within 30 - 60 s, enabling the full release of —NCO and its reaction with the hydroxyl group of component A to form the main crosslinking network. The upper limit of 60 mW / cm² avoids premature depletion of the photoinitiator due to excessive energy or unexpected cleavage of the dynamic disulfide bond caused by local overheating. Subsequently, auxiliary curing at 40 - 50 °C for 0.5 - 1 h promotes the reversible recombination of the dynamic disulfide bond using mild heat energy. The upper limit of the temperature of 50 °C prevents excessive migration of the silicone oxide hydrophobic layer from affecting the surface flatness. At the same time, the lower limit of 0.5 h ensures sufficient reconstruction of the dynamic bond network to relieve the internal stress in the main crosslinking network, and the upper limit of 1 h avoids waste of energy consumption. This parameter combination enables the rapid establishment of the main network skeleton in the UV triggering stage and optimizes the dynamic network distribution in the thermal assistance stage. The two work together to simultaneously improve the crosslinking density and self-healing efficiency. At the same time, the low-temperature curing conditions reduce energy consumption and broaden the applicability to heat-sensitive substrates, ultimately forming an environmentally friendly coating film with hardness, flexibility, and self-healing functions.
[0051] The method of the present invention will be described in detail below in conjunction with examples, comparative examples, and experimental data.
[0052] Example 1 This example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Prepare component A Methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g), and silane coupling agent KH-550 (50 g) are added to a reaction kettle. Ammonium persulfate (4.75 g, accounting for 0.5% of the total mass of 950 g of the three acrylic monomers) is added as an initiator. After purging with nitrogen and heating to 80 °C, the reaction is carried out at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Nanoscale silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) are added to a ball mill, and zirconia balls are used as the grinding medium. Ball milling is carried out at a speed of 300 rpm for 2.5 h to prepare a nanoscale SiO2@POSS dispersion. The above resin (600 g), nanodispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoamer (3 g), and deionized water (191 g) are mixed and dispersed in a high-speed disperser at a speed of 1350 rpm for 35 min, and then passed through a 200-mesh sieve to obtain component A.
[0053] Step 2: Prepare component B Pentaerythritol (10 g), adipic acid (60 g), 3-mercaptopropionic acid (20 g), acrylic acid (10 g), and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C, and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g, and hyperbranched polyester HBP was obtained. Hyperbranched polyester HBP (50 g) and iodine (I2, 3.175 g, molar ratio 2:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water. Under nitrogen protection at 25 °C, reflux reaction was carried out for 12 h. The unreacted I2 was removed by filtration to obtain HBP with dynamic disulfide bonds. HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran. N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering off N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. This HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h. Unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photoresponsive isocyanate curing agent. The dynamic disulfide bond-photoresponsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g), and dipropylene glycol dimethyl ether (70 g) were mixed and treated in an ultrasonic disperser at a frequency of 40 kHz for 25 min to obtain component B.
[0054] Step 3: Coating mixing and curing Component A (1200 g) and component B (300 g) were added to a stirring kettle according to a weight ratio of 4:1 and shear-mixed at a speed of 1000 rpm for 5 min. The mixed coating was sprayed on the surface of the substrate, and the wet film thickness was controlled at 100 μm. Immediately, it was irradiated with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then the coated film was transferred to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0055] Example 2 This example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Prepare component A Methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) were added to a reaction kettle. Ammonium persulfate (4.75 g, 0.5% of the total mass of 950 g of the three acrylic monomers) was added as an initiator. After purging with nitrogen, the temperature was raised to 80 °C and the reaction was carried out at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Nanoscale silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) were added to a ball mill, and zirconia balls were used as the grinding medium. Ball milling was carried out at 300 rpm for 2.5 h to prepare a nanoscale SiO2@POSS dispersion. The above resin (600 g), nanoscale dispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoaming agent (3 g) and deionized water (191 g) were mixed and dispersed at 1350 rpm in a high-speed disperser for 35 min, and then passed through a 200-mesh sieve to obtain Component A.
[0056] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), mercaptopropionic acid (20 g), acrylic acid (10 g), and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and iodine (I2, 3.175 g, molar ratio 2:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water. Under nitrogen protection at 25 °C, reflux reaction was carried out for 12 h, and the unreacted I2 was removed by filtration to obtain HBP with dynamic disulfide bonds. HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran, N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering to remove N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. This HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h, and unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photoresponsive isocyanate curing agent. The dynamic disulfide bond-photoresponsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g) and dipropylene glycol dimethyl ether (70 g) were mixed and treated at a frequency of 40 kHz in an ultrasonic disperser for 25 min to obtain Component B.
[0057] Step 3: Coating Mixing and Curing Add Component A (900 g) and Component B (300 g) into a stirring kettle at a weight ratio of 3:1, and shear and mix at a speed of 1000 rpm for 5 min. Spray the mixed coating on the surface of the substrate, control the wet film thickness at 100 μm, immediately irradiate it with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then transfer the coated film to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0058] Example 3 This example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Preparation of Component A Add methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) into a reaction kettle, add ammonium persulfate (4.75 g, accounting for 0.5% of the total mass of 950 g of the three acrylic monomers) as an initiator, heat up to 80 °C after introducing nitrogen protection, and react at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Add nano-silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) into a ball mill, use zirconia balls as the grinding medium, and ball mill at a speed of 300 rpm for 2.5 h to prepare a nano-SiO2@POSS dispersion. Mix the above resin (600 g), nano-dispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoaming agent (3 g) and deionized water (191 g), disperse in a high-speed disperser at a speed of 1350 rpm for 35 min, and pass through a 200-mesh sieve to obtain Component A.
[0059] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), 3-mercaptopropionic acid (20 g), acrylic acid (10 g), and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C, and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and iodine (I2, 4.23 g, molar ratio 1.5:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water, and reflux reaction was carried out for 12 h under nitrogen protection at 25 °C. Unreacted I2 was removed by filtration, and by-product hydrogen iodide was removed by filtration to obtain HBP with dynamic disulfide bonds. HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran, N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering off N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. This HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h, and unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photoresponsive isocyanate curing agent. The dynamic disulfide bond-photoresponsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g), and dipropylene glycol dimethyl ether (70 g) were mixed and treated in an ultrasonic disperser at a frequency of 40 kHz for 25 min to obtain Component B.
[0060] Step 3: Coating mixing and curing Component A (1200 g) and Component B (300 g) were added to a stirring kettle according to a weight ratio of 4:1, and shear mixing was carried out at a speed of 1000 rpm for 5 min. The mixed coating was sprayed on the surface of the substrate, and the wet film thickness was controlled at 100 μm. Immediately, it was irradiated with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then the coated film was transferred to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0061] Comparative Example 1 This comparative example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Prepare Component A Methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) were added to a reaction kettle. Ammonium persulfate (4.75 g, 0.5% of the total mass of 950 g of the three acrylic monomers) was added as an initiator. After purging with nitrogen, the temperature was raised to 80 °C and the reaction was carried out at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Nano-silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) were added to a ball mill, and zirconia balls were used as the grinding medium. Ball milling was carried out at 300 rpm for 2.5 h to prepare a nano-SiO2@POSS dispersion. The above resin (600 g), nano-dispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoaming agent (3 g) and deionized water (191 g) were mixed and dispersed in a high-speed disperser at 1350 rpm for 35 min, and then passed through a 200-mesh sieve to obtain Component A.
[0062] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), mercaptopropionic acid (20 g), acrylic acid (10 g), and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and iodine (I2, 3.175 g, molar ratio 2:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water, and reflux reaction was carried out at 25 °C under nitrogen protection for 12 h. Unreacted I2 was removed by filtration to obtain HBP with dynamic disulfide bonds. HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran, N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering off N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. This HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h, and unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photoresponsive isocyanate curing agent. The dynamic disulfide bond-photoresponsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g) and dipropylene glycol dimethyl ether (70 g) were mixed and treated in an ultrasonic disperser at a frequency of 40 kHz for 25 min to obtain Component B.
[0063] Step 3: Coating Mixing and Curing Add Component A (600 g) and Component B (300 g) into a stirring kettle at a weight ratio of 2:1, and shear-mix at a speed of 1000 rpm for 5 min. Spray the mixed coating onto the surface of the substrate, control the wet film thickness at 100 μm, immediately irradiate with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then transfer the coated film to an oven at 45 °C for assisted curing for 45 min to obtain the final coated film.
[0064] Comparative Example 2 This comparative example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method comprises the following steps: Step 1: Preparation of Component A Add methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) into a reaction kettle, add ammonium persulfate (4.75 g, accounting for 0.5% of the total mass of the three acrylic monomers, 950 g) as an initiator, heat up to 80 °C after introducing nitrogen protection, and react at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Add nano-silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) into a ball mill, use zirconia balls as the grinding medium, and ball mill at a speed of 300 rpm for 2.5 h to prepare a nano-SiO2@POSS dispersion. Mix the above resin (600 g), nano-dispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoaming agent (3 g) and deionized water (191 g), disperse in a high-speed disperser at a speed of 1350 rpm for 35 min, and pass through a 200-mesh sieve to obtain Component A.
[0065] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), 3-mercaptopropionic acid (20 g), acrylic acid (10 g), and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C, and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and iodine (I2, 1.59 g, molar ratio 4:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water, and reflux reaction was carried out for 12 h under nitrogen protection at 25 °C. Unreacted I2 was removed by filtration to obtain HBP with dynamic disulfide bonds. HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran, and N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added. The reaction was carried out at 60 °C for 24 h. After filtering off N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. This HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h, and unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photoresponsive isocyanate curing agent. The dynamic disulfide bond-photoresponsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g), and dipropylene glycol dimethyl ether (70 g) were mixed and treated in an ultrasonic disperser at a frequency of 40 kHz for 25 min to obtain Component B.
[0066] Step 3: Coating mixing and curing Component A (1200 g) and Component B (300 g) were added to a stirring kettle according to a weight ratio of 4:1, and shear mixing was carried out at a speed of 1000 rpm for 5 min. The mixed coating was sprayed on the surface of the substrate, and the wet film thickness was controlled at 100 μm. Immediately, it was irradiated with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then the coated film was transferred to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0067] Comparative Example 3 This comparative example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Preparation of Component A Methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) were added to a reaction kettle. Ammonium persulfate (6.65 g, 0.7% of the total mass of 950 g of the three acrylic monomers) was added as an initiator. After purging with nitrogen, the temperature was raised to 80 °C and the reaction was carried out at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Nanometer silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) were added to a ball mill, and zirconia balls were used as the grinding medium. Ball milling was carried out at 300 rpm for 2.5 h to prepare a nanometer SiO2@POSS dispersion. The above resin (600 g), nanodispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether compound defoamer (3 g) and deionized water (191 g) were mixed and dispersed at 1350 rpm in a high-speed disperser for 35 min, and then passed through a 200-mesh sieve to obtain Component A.
[0068] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), mercaptopropionic acid (20 g), acrylic acid (10 g) and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and iodine (I2, 3.175 g, molar ratio 2:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water. Under nitrogen protection at 25 °C, reflux reaction was carried out for 12 h, and unreacted I2 was removed by filtration to obtain HBP with dynamic disulfide bonds. HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran, N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering off N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. This HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h, and unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photo-responsive isocyanate curing agent. The dynamic disulfide bond-photo-responsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g) and dipropylene glycol dimethyl ether (70 g) were mixed and treated at a frequency of 40 kHz in an ultrasonic disperser for 25 min to obtain Component B.
[0069] Step 3: Coating Mixing and Curing Add Component A (1200 g) and Component B (300 g) into a stirring kettle according to a weight ratio of 4:1, and shear and mix at a speed of 1000 rpm for 5 min. Spray the mixed coating on the surface of the substrate, control the wet film thickness at 100 μm, immediately irradiate with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then transfer the coated film to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0070] Comparative Example 4 This comparative example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Preparation of Component A Add methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) into a reaction kettle, add ammonium persulfate (4.75 g, accounting for 0.5% of the total mass of 950 g of the three acrylic monomers) as an initiator, heat up to 80 °C after introducing nitrogen protection, and carry out a constant temperature reaction for 4.5 h to obtain a silicone-modified acrylic resin. Add nano-silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) into a ball mill, use zirconia balls as the grinding medium, and ball mill at a speed of 300 rpm for 2.5 h to prepare a nano-SiO2@POSS dispersion. Mix the above resin (600 g), nano-dispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoaming agent (3 g) and deionized water (191 g), disperse in a high-speed disperser at a speed of 1350 rpm for 35 min, and pass through a 200-mesh sieve to obtain Component A.
[0071] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), 3-mercaptopropionic acid (20 g), acrylic acid (10 g), and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C, and melt polycondensation was carried out for 5.5 h. The reaction was stopped when the acid value dropped to 4.8 mg KOH / g to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and iodine (I2, 3.175 g, molar ratio 2:1) were dissolved in a mixed solution of 100 mL of ethanol and 100 mL of water. Under nitrogen protection at 25 °C, reflux reaction was carried out for 12 h. Unreacted I2 was removed by filtration to obtain HBP with dynamic disulfide bonds. Hyperbranched polyester HBP with dynamic disulfide bonds (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran. N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering off N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups. Hyperbranched polyester HBP with dynamic disulfide bonds and o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h. Unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain a dynamic disulfide bond-photoresponsive isocyanate curing agent. The dynamic disulfide bond-photoresponsive isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g), and dipropylene glycol dimethyl ether (70 g) were mixed and treated in an ultrasonic disperser at a frequency of 40 kHz for 25 min to obtain component B.
[0072] Step 3: Coating mixing and curing Component A (1200 g) and component B (300 g) were added to a stirring kettle according to a weight ratio of 4:1 and shear-mixed at a speed of 1000 rpm for 5 min. The mixed coating was sprayed on the surface of the substrate, and the wet film thickness was controlled at 100 μm. Immediately, it was irradiated with a 365 nm UV lamp (light intensity 30 mW / cm²) for 45 s, and then the coated film was transferred to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0073] Comparative Example 5 This comparative example provides a preparation method of an environmentally friendly waterborne two-component polyurethane coating, and the method includes the following steps: Step 1: Preparation of component A Methyl methacrylate (400 g), butyl acrylate (350 g), 2-hydroxyethyl methacrylate (200 g) and silane coupling agent KH-550 (50 g) were added to a reaction kettle. Ammonium persulfate (4.75 g, 0.5% of the total mass of 950 g of the three acrylic monomers) was added as an initiator. After purging with nitrogen, the temperature was raised to 80 °C and the reaction was carried out at a constant temperature for 4.5 h to obtain a silicone-modified acrylic resin. Nanoscale silica (particle size 20 nm, 100 g) and octavinylsilsesquioxane (100 g) were added to a ball mill, and zirconia balls were used as the grinding medium. Ball milling was carried out at 300 rpm for 2.5 h to prepare a nanoscale SiO2@POSS dispersion. The above resin (600 g), nanoscale dispersion (200 g), polyether-modified silicone wetting agent (6 g), mineral oil-polyether composite defoaming agent (3 g) and deionized water (191 g) were mixed and dispersed in a high-speed disperser at 1350 rpm for 35 min, and then passed through a 200-mesh sieve to obtain Component A.
[0074] Step 2: Preparation of Component B Pentaerythritol (10 g), adipic acid (60 g), mercaptopropionic acid (20 g), acrylic acid (10 g) and 2-hydroxyethyl methacrylate (10 g) were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 170 °C and melt polycondensation was carried out for 5.5 h until the acid value dropped to 4.8 mg KOH / g, and then the reaction was stopped to obtain hyperbranched polyester HBP. Hyperbranched polyester HBP (50 g) and o-nitrobenzyl alcohol (275 g, molar ratio 1:10) were dissolved in tetrahydrofuran, N,N'-dicyclohexylcarbodiimide (DCC, 22 g) and 4-dimethylaminopyridine (DMAP, 1.1 g) were added, and the reaction was carried out at 60 °C for 24 h. After filtering to remove N,N'-dicyclohexylurea (DCU), the solvent was removed by rotary evaporation to obtain HBP with o-nitrobenzyl ester groups. This HBP with o-nitrobenzyl ester groups (50 g) and hexamethylene diisocyanate (750 g, molar ratio 1:15) were reacted at 60 °C for 6.5 h, and unreacted HDI was removed by vacuum distillation (residual amount ≤ 0.5%) to obtain an isocyanate curing agent. The isocyanate curing agent (900 g), benzophenone derivative photoinitiator (20 g), fluorocarbon-modified polyacrylate leveling agent (10 g) and dipropylene glycol dimethyl ether (70 g) were mixed and treated in an ultrasonic disperser at a frequency of 40 kHz for 25 min to obtain Component B.
[0075] Step 3: Coating mixing and curing Component A (1200 g) and Component B (300 g) were added to a stirring kettle at a weight ratio of 4:1 and shear-mixed at 1000 rpm for 5 min. The mixed coating was sprayed on the surface of the substrate, and the wet film thickness was controlled at 100 μm. Immediately, it was irradiated with a 365 nm UV lamp (light intensity 50 mW / cm²) for 45 s, and then the coated film was transferred to an oven at 45 °C for auxiliary curing for 45 min to obtain the final coated film.
[0076] Experimental methods 1. Pencil hardness: According to GB / T 6739-2022 "Paints and varnishes - Determination of film hardness by pencil test", using an electric pencil hardness tester (load 750 g), a Zhonghua brand pencil (6B-9H) was uniformly drawn across the surface of the coated film at a 45° angle, and it was observed whether scratches appeared. The highest pencil hardness grade without visible scratches was taken as the test result. For example, 2H means that the 2H pencil did not scratch, but the 3H pencil scratched.
[0077] 2. Water resistance: According to GB / T 1733-1993 "Method for the determination of water resistance of films", the coated film test panel (100×50×1 mm³) was completely immersed in deionized water at 25±1 °C for 24 h. After taking it out, the surface moisture was wiped dry, and the mass difference before and after immersion was weighed to calculate the water absorption rate: Water absorption rate (%) = (mass after immersion - initial mass) / initial mass × 100%.
[0078] 3. Self-healing rate: Using a sharp blade (tip angle 30°), a straight scratch with a length of 50 mm and a width of 20±2 μm was made on the surface of the coated film, and it was placed in an oven at 60 °C and heated for 10 min. A laser confocal microscope (Keyence VK-X1000) was used to measure the scratch width before and after repair, and the repair rate was calculated: Repair rate (%) = (original width - width after repair) / original width × 100%.
[0079] 4. Storage stability: Referring to GB / T 6753.3-1986 "Test method for storage stability of paints", Components A and B were respectively sealed in 500 mL tinplate cans and placed in a constant temperature oven at 40±2 °C for accelerated storage for 30 days. A Brookfield DV2T viscometer (rotor S64, rotation speed 60 rpm, 25 °C) was used to measure the initial and post-storage viscosities, and the change rate was calculated: Viscosity change rate (%) = (post-storage viscosity - initial viscosity) / initial viscosity × 100%.
[0080] 5. Impact resistance: According to GB / T 1732-2020 "Determination of Impact Resistance of Paint Films", using a QCJ type paint film impact tester, fix the coated test panel (120×50×1 mm³) on the impact base. A punch with a weight of 1000 g and a diameter of 15.9±0.3 mm freely falls from a height of 50 cm to impact the front of the test panel. Visually inspect whether there are cracks or peeling in the impact area. If there are no defects, it is judged as "pass".
[0081] The experimental results are shown in Table 1 Table 1 Comparison Table of Key Performance Indicators between Examples and Comparative Examples
[0082] Analysis of Experimental Results The pencil hardness of Example 1 reached 2H, indicating a significant synergistic strengthening effect between the siloxane-modified resin and nano-SiO2@POSS; the water absorption rate in 24 hours was only 1.2%, attributed to the dual barrier effects of the siloxane hydrophobic layer and the POSS-filled micropores; the self-healing rate of 80% verified the effective response of the dynamic disulfide bonds within the range of 6.5 wt%; the change in storage viscosity of 5% indicated that the pre-reaction of A / B components was controllable under the claimed parameters, and the light shielding stability of the hyperbranched curing agent was good. Passing the impact resistance test reflected the balance between the flexibility and rigidity of the crosslinked network. The design of the molar ratio of hydroxyl group to -NCO of 1:1.05 - 1.2 avoided the brittleness caused by excessive crosslinking.
[0083] In Example 2, the mixing ratio was adjusted to 3:1. The decrease in the proportion of component A made the molar ratio of hydroxyl group to -NCO close to 1:1.05, and the crosslinking density decreased slightly, but the pencil hardness still remained at 2H, and the water absorption increased slightly to 1.5%, indicating that the lower limit of 3:1 in Claim 1 could still maintain the basic performance; the self-healing rate of 78% and the change in storage viscosity of 6% showed that the interaction between the dynamic bond network and the main crosslinking was not significantly affected, verifying the rationality of the mixing ratio range. Passing the impact resistance test further proved that even at the lower limit of the ratio, the synergy between the resin molecular weight and the nano-enhanced phase could still ensure the toughness of the coating film.
[0084] Example 3 increased the dynamic bond content to 8 wt%, and the self-healing rate increased to 88%. Since more dynamic disulfide bonds participated in the recombination, the pencil hardness decreased to H, and the relative proportion of the main cross-linked network decreased, resulting in a decrease in rigidity. The water absorption slightly increased to 1.8% because the increase in dynamic bonds might introduce local hydrophobic defects, but it was still significantly better than traditional coatings. The change in storage viscosity was 7%, indicating that the dynamic bond content within the upper limit of the range of 5-8 wt% did not cause side reactions, verifying the compatibility of the 5-8 wt% range with storage stability. The impact resistance demonstrated that the flexibility of the dynamic bonds compensated for the loss of hardness, and limiting the dynamic disulfide bond content to 5-8 wt% improved the self-healing ability without disrupting the mechanical balance. (The content of dynamic bonds can be calculated through the following process, formula omitted: According to the molar ratio of hyperbranched polyester HBP to diiodomethane (such as 1:1.2), calculate the total amount of mercapto groups (-SH) participating in the reaction. Every 2 -SH react with 1 diiodomethane to form 1 dynamic disulfide bond (-S-S-)) Comparative Example 1 had a mixing ratio of 2:1, and the molar ratio of hydroxyl to -NCO was imbalanced to 1:0.7. Insufficient cross-linking density led to a sharp drop in pencil hardness to grade B, the coating film structure was loose, and the water absorption rate was as high as 8.5%. The self-healing rate of 75% seemingly approached that of Example 1, but due to defects in the main network, the mechanical properties could not be restored after repair. The change in storage viscosity of 25% reflected that the excess of component A caused the premature consumption of -NCO in component B, verifying the necessity of the lower limit of the mass ratio of component A to component B of 3:1 to inhibit pre-reaction. The failure of the impact resistance further demonstrated the insufficient strength of the coating film under low cross-linking density.
[0085] In Comparative Example 2, the dynamic bond content was 4 wt%, and the self-healing rate was only 45%. The dynamic network was sparse and difficult to effectively bridge scratches. The pencil hardness increased to 3H because the proportion of the main cross-linked network was too high, but the failure of the impact resistance indicated an increase in brittleness. The water absorption of 1.0% seemed excellent, but it was actually because there were fewer microcracks on the surface of the brittle coating film, but it was prone to rapid failure due to impact damage during actual use.
[0086] In Comparative Example 3, the initiator dosage was 0.7%. Excessive free radicals led to too low a resin molecular weight (<30,000 Da), and the coating film was hard and brittle (pencil hardness 3H but failed in impact resistance). The water absorption of 2.5% was due to the enhanced hydrophilicity of the low molecular weight resin. The change in storage viscosity of 35% reflected the intensified side cross-linking of unreacted monomers and siloxanes, proving the necessity of the initiator dosage of 0.4 - 0.6% of the total mass of methyl methacrylate, butyl acrylate, and 2-hydroxyethyl methacrylate to control the molecular weight distribution. The self-healing rate of 82% was abnormally high because the low molecular chains were more likely to migrate, but it could not withstand secondary damage due to brittleness in actual applications.
[0087] In Comparative Example 4, the UV light intensity was 30 mW / cm². The incomplete cleavage of ONB led to an insufficient release rate of —NCO. The defects in the crosslinked network reduced the pencil hardness to H and increased the water absorption rate to 4.2%. The self-healing rate was 70% because the main network was incomplete and the dynamic bond recombination was difficult to effectively anchor. The 18% change in storage viscosity indicated that some —NCO was not released, and the residual activity of Component B triggered a slow pre-reaction.
[0088] In Comparative Example 5, the absence of dynamic disulfide bonds led to the complete loss of the self-healing ability of the coating film (0% repair rate). Although the hardness (2H) was comparable to that of Example 1, the water absorption rate increased to 3.8%, indicating that the auxiliary crosslinked network of dynamic bonds plays a key role in reducing water molecule penetration. The change in storage viscosity increased to 15%, indicating that the reversible recombination of dynamic bonds can relieve the rigid packing of the curing agent molecular chains and inhibit the increase in viscosity during storage.
[0089] In Examples 1-3, through dynamic bond design, mixing ratio control, and process optimization within the scope of the claim parameters, the synergy of high hardness, self-healing, and water absorption was achieved. In Comparative Examples 1-4, the performance degradation caused by exceeding a single parameter was used to prove the technical necessity of each limit value in the claim in reverse. For example, the mixing ratio ensures the crosslinking density, the content of dynamic bonds balances self-healing and rigidity, the dosage of the initiator controls the resin molecular weight, and the UV light intensity ensures the curing trigger efficiency. Comparative Example 5 verified from the component level that dynamic disulfide bonds are the core carriers of the self-healing function. By setting the parameters and raw materials of this application, the pain points of poor storage stability, high curing temperature, and lack of self-healing function in traditional waterborne coatings are solved, reflecting the technical progress and practical value of the invention points.
[0090] It should be noted that in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variant are intended to cover non-exclusively, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Without further limitation, an element defined by the statement "including a..." does not exclude the existence of another identical element in the process, method, article or device including the element.
[0091] The above are only specific embodiments of the present invention, enabling those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be obvious to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown herein, but rather to the broadest scope consistent with the principles and novel features claimed herein.
Claims
1. An environmentally friendly water-based two-component polyurethane coating, characterized in that: It comprises component A and component B, wherein the mass ratio of component A to component B is 3:1-5:1; The A component contains the following ingredients in percentage by weight: Water-based hydroxy acrylic resin 50-70%, nano-SiO2@POSS 3-8%, wetting agent 0.2-0.8%, defoaming agent 0.1-0.5%, and the balance is deionized water; The B component contains the following ingredients in percentage by weight: Dynamic disulfide bond-photoresponsive isocyanate curing agent 80-95%, photoinitiator 1-3%, leveling agent 0.5-2%, cosolvent 3-10%; Wherein, the dynamic disulfide bond-photoresponsive isocyanate curing agent is a hyperbranched polyester derivative, including a hyperbranched polyester skeleton, a dynamic disulfide bond, an o-nitrobenzyl ester group and a carbamate bond; The molar ratio of the hydroxyl group of the water-based hydroxy acrylic resin in component A to the isocyanate group of the dynamic disulfide bond-photoresponsive isocyanate curing agent in component B is 1:1.05-1:1.
2.
2. The environmentally friendly water-based two-component polyurethane coating according to claim 1, characterized in that: The water-based hydroxy acrylic resin is a siloxane-modified acrylic copolymer, which is copolymerized by methyl methacrylate, butyl acrylate, and hydroxyethyl methacrylate, and a silane coupling agent KH-550 is added during the copolymerization. The side chain of the water-based hydroxy acrylic resin contains a siloxane group, and the hydroxyl value is 80-120 mg KOH / g.
3. The environmentally friendly water-based two-component polyurethane coating according to claim 1, characterized in that: The mass ratio of SiO2 to POSS in the nano-SiO2@POSS is 1:1, and the particle size of SiO2 is 15-25 nm.
4. The environmentally friendly water-based two-component polyurethane coating according to claim 1, characterized in that: In the dynamic disulfide bond-photoresponsive isocyanate curing agent, the dynamic disulfide bond content is 5-8 wt %.
5. The environmentally friendly water-based two-component polyurethane coating according to claim 1, characterized in that: The wetting agent is polyether modified siloxane with a molecular weight of 800-1200 g / mol; the defoamer is a mineral oil-polyether composite defoamer with an HLB value of 3-5; the photoinitiator is a benzophenone derivative; the leveling agent is fluorocarbon modified polyacrylate; and the cosolvent is dipropylene glycol dimethyl ether.
6. A method for preparing an environmentally friendly water-based two-component polyurethane coating as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S11, reacting methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and silane coupling agent KH-550 at a mass ratio of 40:35:20:5 under the condition of an initiator, and reacting at 80±2° C. for 4-5 hours to obtain a siloxane-modified acrylic resin; S12, ball milling nano-SiO2 and octavinylsilsesquioxane at a mass ratio of 1:1 for 2-3 hours to obtain nano-SiO2@POSS dispersion; S13, mixing the resin obtained in S11 and the dispersion obtained in S12 with a wetting agent, a defoaming agent, and deionized water, and dispersing at 1200-1500 rpm for 30-40 min to obtain component A; S21, pentaerythritol, adipic acid, mercaptopropionic acid, acrylic acid, and hydroxyethyl methacrylate were melt-polycondensed at 160-180° C. for 6 h in a mass ratio of 10:50:20:10:10 to obtain a hyperbranched polyester HBP; S22, reacting the hyperbranched polyester HBP with I2 at a molar ratio of 2:1 to construct a dynamic disulfide bond to obtain HBP with a dynamic disulfide bond; S23, mixing the HBP having a dynamic disulfide bond with o-nitrobenzyl alcohol at a molar ratio of 1:10 for esterification reaction to obtain HBP having a dynamic disulfide bond and an o-nitrobenzyl ester group; S24, reacting HBP having a dynamic disulfide bond and an o-nitrobenzyl ester group with hexamethylene diisocyanate at a molar ratio of 1:15 at 60° C. for 6-7 hours to prepare a dynamic disulfide bond-photoresponsive isocyanate curing agent; S25, ultrasonically dispersing the dynamic disulfide bond-photoresponsive isocyanate curing agent, the photoinitiator, the leveling agent, and the cosolvent for 20-30 minutes to obtain component B; S30, mixing the component A and the component B in proportion, and irradiating with 365 nm UV for 30-60 seconds to trigger curing.
7. The preparation method according to claim 6, characterized in that: In the copolymerization reaction of S11, the initiator of the copolymerization reaction is ammonium persulfate, and the amount of the initiator used is 0.4-0.6% of the total mass of the methyl methacrylate, the butyl acrylate and the hydroxyethyl methacrylate.
8. The preparation method according to claim 6, characterized in that: In the S22, the dynamic disulfide bond construction is carried out in a mixed solvent of ethanol / water with a volume ratio of 1:1, with nitrogen protection, the reaction time is 12 hours, and the reaction temperature is 25°C.
9. The preparation method according to claim 6, characterized in that: In the S23, the esterification reaction temperature is 55-65°C.
10. The preparation method according to claim 6, characterized in that: In the S30, the UV irradiation intensity is 40-60 mW / cm², and after irradiation, the coating film is auxiliary cured at 40-50° C. for 0.5-1 h.
Citation Information
Patent Citations
Water-based two-component acrylic acid polyurethane automobile paint and preparation method thereof
CN102020917A
Polyurethane acrylate dispersoid and preparation method thereof, and high-performance water-based wood coating and preparation method thereof
CN114044873A
Hydroxyl polyacrylate dispersion, preparation method thereof, high-performance water-based two-component polyurethane coating and preparation method of high-performance water-based two-component polyurethane coating
CN114349896A